Keyword | CPC | PCC | Volume | Score |
---|---|---|---|---|

x ln x 2 ln x 6 | 1.43 | 0.5 | 7072 | 93 |

ln ( x / y) = ln ( x) - ln ( y) ln (3 / 7) = ln (3) - ln (7) Power rule. ln ( x y) = y ∙ ln ( x) ln (2 8) = 8 ∙ ln (2) ln derivative. f ( x) = ln ( x) ⇒ f ' ( x) = 1 / x. #N#ln integral. ∫ ln ( x) dx = x ∙ (ln ( x) - 1) + C.

Is there even such a thing as ln2x? ln2x is simply another way of writing (lnx)2 and so they are equivalent. There is only one condition where ln2x = lnx2 set out below. Since lnx ≠ 0

The natural logarithm function ln (x) is the inverse function of the exponential function e x. The logarithm of the multiplication of x and y is the sum of logarithm of x and logarithm of y. The logarithm of the division of x and y is the difference of logarithm of x and logarithm of y.

Product rule. ln ( x ∙ y) = ln ( x) + ln ( y) ln (3 ∙ 7) = ln (3) + ln (7) Quotient rule. ln ( x / y) = ln ( x) - ln ( y) ln (3 / 7) = ln (3) - ln (7) Power rule. ln ( x y) = y ∙ ln ( x) ln (2 8) = 8 ∙ ln (2)